An empirical investigation into the critical success factors used by IT companies of various sizes to adopt internet technology / Lloyd Tam Yew King - Tam, Lloyd Yew King (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2001)
Internet technology is transforming the way in which business strategies are formulated in the corporate world. Indeed, it is proving to be the most effective and influential strategic tool of the century by connecting thousands of companies and millions of people every minute. This paper highlights the salient factors used by IT companies of various sizes in the adoption of internet technology. Five organisational and two market place factors were used in this study. The final analysis confirm that larger IT companies were more influenced by the following factors -perceived direct benefits, organisational compatibility, trading partner pressure, organisational support, and perceived in-direct benefits than smaller IT companies. On the other hand, smaller IT companies were affected by technical complexity than larger IT companies. However, competitive pressure is not an influential factor.